EVALUATION OF DIURETIC ACTIVITY OF TRICHODESMA INDICUM R.BR. IN RATS - MANANI LATA M.; KAKRANI PURVI; DR. SALUJA AJAY K. (International Journal of Pharma and Bio Sciences, 2014)
The plant Trichodesma indicum R.Br. is easily available and distinctly used in inflammation. Whole plant is used as diuretic, as an emollient poultice, as a cure for fever, in ear pain. This study was undertaken to carry out pharmacological studies on aerial parts of plant. Methanolic extract and aqueous extract of aerial parts of Trichodesma indicum were used for screening diuretic activity using Lipschitz model. Diuretic activity, in view of urine volume, the methanolic extract at dose of 300 mg/kg has significant diuretic activity with lipschitz value 1.25 as compared to standard. Urinary sodium concentration was found to be more in methanolic extract but potassium was found to be more in aqueous extract. It also shows that, methanolic extract has effect like K+ sparing diuretics. It has also saluretic activity. In conclusion, Trichodesma indicum R.Br. possess significant diuretic activity these actions of Trichodesma indicum R.Br. can be attributed to Phytoconstituents present in it.